2015
DOI: 10.1161/strokeaha.114.006881
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Thromboembolic Events in Atrial Fibrillation With Chronic Kidney Disease

Abstract: Background and Purpose-Chronic kidney disease may increase the risk for ischemic stroke or systemic embolism in patients with nonvalular atrial fibrillation (AF). We conducted a meta-analysis to summarize all published studies to investigate the link between chronic kidney disease and risk of thromboembolic events in AF. Methods-We performed a literature search using MEDLINE (source PubMed, 1966 and EMBASE (1980 to July 2014) with no restrictions. Pooled effect estimates were obtained by using random-effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 61 publications
(40 citation statements)
references
References 45 publications
3
33
0
4
Order By: Relevance
“…Pooled RRs were expressed with 95% CIs. We calculated the I 2 (95% CI) statistic to assess heterogeneity across studies, applying the following interpretation for I 2 : <50%=low heterogeneity; 50% to 75%=moderate heterogeneity; >75%=high heterogeneity . Subgroup analyses and meta‐regression models were carried out to investigate potential sources of between‐study heterogeneity.…”
Section: Methodsmentioning
confidence: 99%
“…Pooled RRs were expressed with 95% CIs. We calculated the I 2 (95% CI) statistic to assess heterogeneity across studies, applying the following interpretation for I 2 : <50%=low heterogeneity; 50% to 75%=moderate heterogeneity; >75%=high heterogeneity . Subgroup analyses and meta‐regression models were carried out to investigate potential sources of between‐study heterogeneity.…”
Section: Methodsmentioning
confidence: 99%
“…In the present study, two other risk factors associated with the occurrence of ES after AF ablation were poor kidney function and prior TE. A previous meta‐analysis has demonstrated that patients with impaired renal function were significantly at risk of developing TE as those having other well‐known major risk factors . Prior TE is also a well‐known risk factor of recurrent ES after AF ablation and has been reported to increase the risk by 4.5 to 6.3‐folds .…”
Section: Discussionmentioning
confidence: 99%
“…Summary RRs were estimated by pooling the study-specific estimates using random rather than fixed effects models in order to take into account the between-study heterogeneity. 11 To assess for heterogeneity of RRs across studies, the I 2 (95% CI) statistic was calculated with the following interpretation: low heterogeneity defined as I 2 <50%; moderate heterogeneity defined as I 2 50% to 75%; high heterogeneity defined as I 2 >75%. 12 Heterogeneity was also calculated by comparing results from studies stratified according to prespecified study-level characteristics with meta-regression and subgroup analyses.…”
Section: Methodsmentioning
confidence: 99%